Knowledge attitude and practice of pregnant women on postnatal depression in Henan Province China - Zhenzhen Wang; Qian Zhang; Rong Nie; Liping Zhou; Congcong Zhao; Yuan Cao; Xianghong Cheng (Scientific Reports)
Abstract Postnatal depression is a common maternal mental health problem with substantial public health implications, yet limited attention has been given to pregnant women’s perceptions and responses to it. There are few studies explore pregnant women’s Knowledge, Attitude, and Practice (KAP) towards postnatal depression. This study aimed to investigate the knowledge, attitude, and practice (KAP) of pregnant women regarding postnatal depression in Henan Province, China, between June and November 2023. A random sampling method was used to recruit eligible pregnant women attending antenatal care. This cross-sectional survey was conducted between June and November 2023 at the Henan Provincial People’s Hospital among pregnant women. Demographic information and KAP scores were collected by a self-designed questionnaire. Descriptive statistics, t-tests, ANOVA, Pearson correlation, and structural equation modeling (SEM) were conducted using R version 4.3.1. A total of 500 (95.97%) valid questionnaires were enrolled, with mean age of 30.78 ± 4.09 years. The mean KAP scores were 14.91 ± 2.385 (possible range: 0–20), 41.06 ± 4.160 (possible range: 11–55), 45.34 ± 7.309 (possible range: 13–65), respectively. The structural equation modeling results showed that residence and education, number of deliveries had direct effect on knowledge. Knowledge, education, and family relationships had direct effect on attitude. Knowledge, attitude, and experiencing mental illness, number of deliveries and education had direct effect on practice. Pregnant women had adequate knowledge, positive attitude, and suboptimal practice towards postnatal depression. The findings highlight the need for targeted educational interventions, family engagement, and a focus on mental health experiences to enhance clinical practices in addressing postnatal depression among pregnant women.